BREEDING VALUE ESTIMATION USING TEST DAY RECORDS IN MURRAH GRADED BUFFALOES - Bhumit K Patel; Ashish C Patel; S B Patel; R. S. Joshi; D N Rank (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out using test day yield for sire evaluation in Murrahgraded buffalo. A total of 2329 test day lactation records of daughters of 79 sires distributed in 47 villages under field progeny testing programme in Anand milk shed area were utilized. The objective of the study was to estimate the breeding value of sires and to compare various methods of sire evaluation viz. simple daughter’s average (D), contemporary comparison (CC), leastsquares (LS), best linear unbiased prediction (BLUP), average information restricted maximum likelihood (AIREML) and random regression (RR) for Predicted First Lactation Yield for 305 day (PFLY305 day) and Test day records of Murrah graded buffaloes in terms of accuracy and efficiency. For PFLY305 and Test Day Milk Yield (TDMY) estimates, AIREML and RR methods were found to have minimum error variance respectively and therefore, found most efficient. LS and BLUP methods had equal error variance for PFLY305. For 305 day fat per cent and Test Day Fat Per cent (TDFP) estimates, the AIREML and RR methods with minimum error variance respectively were found to be most efficient methods. For PFLY305 and TDMY, the rank correlations of D, CC, LS, BLUP, AIREML and most efficient RR methods were 0.47, 0.12, 0.34, 0.47 and 0.16, respectively. All the methods are expected to rank sires with fairly high accuracy. For 305 day fat per cent and TDFP, the rank correlations of D, CC, LS, BLUP, AIREML with most efficient RR methods were 0.14, 0.17, 0.06, 0.03 and 0.12, respectively.